ROLE OF PANCHAKARMAS IN TREATMENT OF TIMIR: MODE OF ACTION AND CONTRA-INDICATIONS (International Journal of Ayurveda and Pharma Research, 2020)
Drushti or vision is most important sense of human body. Any condition disturbing visual acuity is considered under the title of Timir in Ayurvedic literature. Different Shodhana and Shamana procedures are used in treatment of Timir. Panchakarma procedures consisting of Vaman, Virechana, Basti, Nasya and Raktamokshana are chiefly used for Shodhana of vitiated humor. But these procedures are associated with various side effects and contra-indication. Injudicious use of such procedures in diseases like Timir affecting visual acuity of subject may lead to worsening of disease. Hence, these procedures should be used cautiously during treatment of ocular diseases especially those impairing vision.